Tests for diagnosing subacromial impingement syndrome and rotator cuff disease. Issue 3 (July 2014) - Phillips, Nick
Clinical examination techniques need to allow the physician to determine the underlying pathology of a patient's condition with confidence. This review examines the evidence for two common conditions: impingement and rotator cuff disease